Exploring Items and Developing an Instrument for Measuring the Relationship Between Age-friendly Environment and the Psychosocial Well-being of Older Adults in Kuching and Bintulu City: An Exploratory Factor Analysis Procedure - Nur Azimah, Azman; Jeffery, Stephen (Universiti Putra Malaysia (UPM), 2025)
Introduction: Malaysia is currently facing the challenges of an ageing population, as ageing does not guarantee a greater quality of life. The World Health Organization has advocated for incorporating age-friendly environments to enhance the well-being of older adults. However, the existing academic literature lacks research instruments for developing countries to assess the relationship between age-friendly environments and older adults' psychosocial well-being. The pilot study aims to create a valid and reliable research instrument, enabling the measurement of the relationship between age-friendly environments and the psychosocial well-being of older adults in Kuching City and Bintulu City, Sarawak. Materials and methods: This study adapted and modified 58 items on age-friendly environments and 11 items on psychosocial well-being from other studies to suit the local setting. The pilot study applied a cross-sectional design and was performed among 219 older adults randomly chosen from Kuching City and Bintulu City. Eight age-friendly environments and psychosocial well-being dimensions were validated using exploratory factor analysis. Results: Exploratory factor analysis confirmed the instrument's validity and reliability, with all items showing acceptable metrics (Cronbach's Alpha > 0.7, KMO > 0.6, and factor loading > 0.6. Conclusion: This study established a validated and reliable instrument for the age-friendly environments and psychosocial well-being of older adults.